Economic figures of sour cherry production at national level of Hungary - Felföldi, J. (International Journal of Horticultural Science, 2011)
After the political changes of 1989, economical processes impaired heavily the Hungarian fruit growing branch, more particularly production of sour cherry. Paralleling with the increasing mass of production, producer’s prices dwindled drastically. At present, Hungarian growers cannot cover the costs of production, nay, hardly raise income. My purpose was to analyse the cost and income relations of the sour cherry branch during the period of 2002-2009 years in order to find out what are the decisive features, which reveal the trends to be considered. The data presented in the paper are means of a heterogeneous population of values, which cannot be utilised for immediate use in management, but they may reveal the challenges and tendencies of economics of the branch.